Предмет: Алгебра, автор: kazminaaa

Упростите выражение: (a+1)(a^{2}+1)(a^{4}+1)(a^{8}+1)(a^{16}+1)(a^{32}+1)

Ответы

Автор ответа: dtnth
0

по формуле разности квадратов (a-b)(a+b)=a^2-b^2

если  aneq 1

(a+1)(a^2+1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)=\ frac{(a-1)(a+1)(a^2+1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1}=\ frac{(a^2-1)(a^2+1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1}=\ frac{(a^4-1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1}=\ frac{(a^8-1)(a^8+1)(a^{16}+1)(a^{32}+1)}{a-1}=\ frac{(a^{16}-1)(a^{16}+1)(a^{32}+1)}{a-1}=\ frac{(a^{32}-1)(a^{32}+1)}{a-1}=\ frac{a^{64}-1}{a-1}

если а=1, то

<var>(a+1)(a^2+1)(a^4+1)(a^8+1)(a^{16}+1)(a^{32}+1)=</var><var>(1+1)(1^2+1)(1^4+1)(1^8+1)(1^{16}+1)(1^{32}+1)=<var>(1+1)(1+1)(1+1)(1+1)(1+1)(1+1)=2*2*2*2*2*2=8*8=64

Похожие вопросы